Meaning of breast cancer in women’s discourse (2021)
ABSTRACT: Objective: To reveal the meaning of breast cancer. Materials and method: A narrative research study that selected, using the snowball technique, 11 women (data saturation) diagnosed with breast cancer, on disease remission, and living in the region of Florianópolis (Brazil). Semi-structured interviews were conducted between August and December 2018, and they were subjected to the Collective Subject Discourse technique. Four central ideas emerged from the analysis of the narratives; this article presents the central ideal called “Meaning of the breast cancer diagnosis”, which has eight sense categories. Results: The central idea covers the following categories: “Suffering when facing the diagnosis”, “Fear of the disease and of death”, “Professional inability for bad news”, “Initiatives to streamline treatment”, “Concern and affection with the family members as a driving force to face cancer”, “Difficulties with the family members”, “Support from the family members, from the professionals and/or from the support group”, and “Faith and spirituality”. Conclusions: The discourse reveals that the meaning of the disease diagnosis is linked to the need for treatment, to the support provided by faith, family members, the health team, and support groups, and to the difficulties faced with family members and professionals. These results should imply the provision of specific Nursing care from the diagnostic phase until after cancer remission/survival.